Drink driving prevention in Ha Nam and Ninh Binh provinces of Viet Nam. (7th October 2012) - Nguyen, N; Passmore, J; Pham, C; La, Q; Nguyen, V; Tran, L; Luong, A; Nguyen, L
Abstract : Background: Drink driving is a major risk factor for road trauma in Viet Nam. Previous studies have shown up to 60% of road traffic injured patients admitted to hospital, had a blood alcohol concentration (BAC) above the level limit. Activities: This programme implemented an enhanced enforcement model where roadside police operations were supplemented by capacity building training for police, essential equipment (breathalysers), and an intensive mass media social marketing campaign on the dangers and consequences of drink–driving. Impact of the programme was measured through a variety of evaluation tools including enforcement data, hospital BAC results and KAP indicators. Results: The social marketing campaign was implemented from August 2010 to November 2011, coupled with almost 7000 person days of enforcement operations running from November 2010 to November 2011 during high alcohol times (12:00–14:00 and 18:00–21:00). Enforcement results from HaNam and NinhBinh showed 23.3% and 21.3% drivers/riders respectively were detected over the legal limit. There's a reduction in people's self reported drink driving between January and August 2011, HaNam from 34.1% to 20% and NinhBinh from 52.2% to 44.2%. However, the low perception of being caught drink driving (24.3%) could possibly add to the current high violation rate. The volume of intake among hospitalised victims reduced. Motorcycle victims having BAC level over 80 mg/dl declined from 21.5% to 11.5% in the 3rd quarter of 2011 in HaNam. Conclusions: Drink driving remains highly prevalent in Viet Nam. However, intensive social marketing coupled with sustained visible enforcement can bring positive changes to people's knowledge and likelihood of drinking and driving.